1995
DOI: 10.1159/000236870
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of an Aspartic Acid Results in Constitutive Activation of c-<i>kit</i>Receptor Tyrosine Kinase in a Rat Tumor Mast Cell Line RBL-2H3

Abstract: The c-kit protooncogene encodes a receptor tyrosine kinase that mediates signals required for differentiation, proliferation and survival of mast cells. We have already shown the constitutive activation of c-kit receptor tyrosine kinase (KIT) in a human mast cell leukemia line (HMC-1) and a murine mastocytoma cell line (P-815). We here examined whether such constitutive activation of KIT occurred in the rat tumor mast cell line RBL-2H3 as well, which is frequently used as a tool for studying functions of mast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 27 publications
3
77
0
Order By: Relevance
“…Similarly, Val and Tyr substitutions of the equivalent Asp802 residue of the closely related c-Kit receptor have been reported in mast cell leukaemia (Kitayama et al, 1995;Tsujimura et al, 1995). Here, we found that all hydrophobic amino acid substitutions of Asp802 of the M-CSFr were highly transforming.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Val and Tyr substitutions of the equivalent Asp802 residue of the closely related c-Kit receptor have been reported in mast cell leukaemia (Kitayama et al, 1995;Tsujimura et al, 1995). Here, we found that all hydrophobic amino acid substitutions of Asp802 of the M-CSFr were highly transforming.…”
Section: Discussionsupporting
confidence: 85%
“…Uncontrolled proliferation and the accumulation of mast cells occurs in MCTs, whereas the normal process of proliferation and differentiation of mast cells are under the control of cytokines, particularly stem cell factor (SCF), also termed as a Kit ligand [8]. Several years ago, point mutations in c-kit that lead to constitutive activation of Kit in the absence of ligand binding were identified in three malignant mast cell lines (human HMC-1, RBL and mouse P815) [3,25,26]. This provides an indication that dysregulation of Kit may promote uncontrolled growth of survival of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…The 293 cell line was established by transduction of human embryonic kidney cells with the adenovirus 5 DNA (Graham et al, 1977) and has been used as a model for studying signal transduction and oncogenesis, including some observations of the biological properties of Asp 816(human)/814(mouse) mutant c-Kit (Furitsu et al, 1993;Kanakura et al, 1994;Moriyama et al, 1996;Tsujimura et al, 1994Tsujimura et al, , 1995Yajima et al, 1998). Furthermore, this cell line has been shown in nude mice to rarely form tumors when injected in low cell numbers (6610 5 ) and to give rise to small-sized tumors when injected in higher numbers of cells (4610 6 ) (Arrick et al, 1992).…”
Section: Discussionmentioning
confidence: 99%